Lepidium meyenii (maca) attenuates titanium dioxide nanoparticle–induced hepatotoxicity in rats - Naser A. ElSawy; Nada Mohamed Mohamed Soliman; Sahar K. Ali; Ahmed Algazeery; Naief A. Dahran; Reham M. Filfilan; Hawazen A. AlGifry; Alaa M. Saleh; Noura Mostafa Mohamed; Hany A. Elkattawy (Tissue and Cell, 2027)

Interrupting a mitochondrial DNA–driven innate immune circuit attenuates hepatic tissue remodeling and fibrotic architecture in experimental steatohepatitis - Rabab S. Hamad; Sura Akram Mohammed; Waseem Ali Hasan; Norhan Ahmed AbuoHashish; Sherin Refat El Afify; Mohamed A.M. Ali; Alaa Eldin Ahmed Mohamed; Attalla F. El-kott; Mohammed A. AlShehri; Kareem Morsy; Alshaimaa A. Farrag; Karem Mohamed Salem; et al. (Tissue and Cell, 2026)

Reservoir Patchiness Influences Fish Condition: Khor-Scale Heterogeneity in Lake Nasser (Egypt) and Implications for Global Inland Fisheries - Alaa M. Younis; Khaled Y. AbouelFadl; Khaled Mohammed-Geba; Doaa Hamed-Mohamed; Mostafa A. Khaled (Fishes, 2026)
Global inland fisheries depend on large reservoirs, yet many assessments assume spatial homogeneity despite complex embayed morphometry. We tested whether khor-scale structure within Lake Nasser, Egypt, explains variation in two commercially important catfishes. Six distinct khors spanning the north–south axis (Ghazal, Sheniara, Garf Hussein, Amada, Toshka, and Hamedo) were sampled with standardized effort (72 net-nights; 12 per khor, 3 representative areas ≥ 500 m apart × 4 campaigns, March–June 2021), yielding 398 fish (268 Chrysichthysauratus, 130 C. rueppelli). Abundance was expressed as standardized CPUE (fish·net-night−1). C. auratus CPUE ranged from 2.83 (Ghazal) to 5.92 (Garf Hussein), while C. rueppelli CPUE was relatively uniform (1.50–1.92). C. auratus attained the largest TL in Ghazal (25.51 ± 2.9 cm) and the highest condition K in Garf Hussein (1.46 ± 0.18). C. rueppelli attained the greatest TL and weight in southern khors, especially Hamedo (23.3 ± 2.33 cm, 146.7 ± 30.5 g), while its highest condition was in Toshka (1.30 ± 0.15). Sex ratio was significantly female-biased for C. auratus (92 M:176 F, 1:1.91, p < 0.001) but not for C. rueppelli (55 M:75 F, 1:1.36, p = 0.079). Results show embayment-scale CPUE and condition, not whole-lake means, capture key population patterns, improving precision of mega-reservoir fisheries management.

From Golden Berry To Golden Nanoprobe: Sustainable Fluorescent Sensing of Torsemide For Doping Control in Athletes - Alaa Ahmed Mostafa; Soad S. Abd El-Hay; Michael Gamal Fawzy; Youstina Mekhail Metias; Walaa Nabil Abd-AlGhafar (Journal of Fluorescence, 2026)

Therapeutic efficacy of L-citrulline versus L-citrulline hydrogel in testicular ischemia/reperfusion injury: Modulation of the SIRT-1/NF-κB and NO synthesis (eNOS/iNOS) pathways - Eman M. Embaby; Aya Megahed; Aya Aly Elzeer; Sally Abdallah Mostafa; Alaa Samy; Amgad E. Salem; Hussein Abdellatif; Eman E. Elwakeel; Mamdouh Eldesoqui (Tissue and Cell, 2026)

Evaluating the effect of Iron biofortification on nutraceutical and aromatic profiles of cereal grains: A case study of pearl millet - Hamza M.A. Abaker; Sulafa B.H. Hashim; Haroon Elrasheid Tahir; Muhammad Arslan; Gustav Komla Mahunu; Zhuhai Li; Xiaodong Zhai; Abdalbasit Adam Mariod; Mohammad Rezaul Islam Shishir; Magdi Ali Osman Mohammed; Ahmed Gaafar Mohammed Elgorashi; Alaa K.M. Khogly; et al. (Food Chemistry, 2026)

Type 2 Diabetes-Induced Molecular and Functional Impairment of Adipose Tissue-Derived Mesenchymal Stromal Cells (ASCs) and Interferon Gamma Priming for Enhanced Diabetic ASC-Based Therapy - Alaa Zeinhom; Ammar Y. Mohamed; Nahla N. Abdel-Aziz; Mostafa Sayed Diab; Amir M. H. Salem; Noha N. Yassen; Eman E. A. Mohammed; Amal M. Mohamed; Ola M. Eid; Shymaa H. Hussein; Marwa Farid; Engy K. Tharwat; et al. (Stem Cell Reviews and Reports, 2026)

Integrated Genome-Wide Association Study and Machine Learning Approach for Characterizing the Determinants of Biofilm Formation in Staphylococcus aureus - Lydia R. Sidarous; Mostafa S. Ibrahim; Mohamed Elhadidy; Alaa Abouelfetouh; Nehal A. Saif; Nirmeen Aboelnaga; Michael Shehat; Mena Youssef; Eman Badr (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Thiazolidinedione-triazole hybrids: design, synthesis, and biological evaluation as dual inhibitors of α-amylase and aldose reductase with antioxidant activity for antidiabetic therapy - Eman E. Nasr; Mohamed R. Elnagar; Nahed Nasser Eid El-Sayed; Marwa I Serag; Mostafa M. Elbadawi; Adel S. El-Azab; Simone Brogi; Hazem A. Ghabbour; Abdelrahman Hamdi; Alaa A.- M. Abdel-Aziz (Molecular Diversity, 2026)

GIS-based land use–intrinsic vulnerability assessment of the Quaternary aquifer in Qena Governorate, Upper Egypt - Salman A. Salman; Mostafa Kamel; Elmontaser M. Seleem; Alaa Mostafa; Hossam A. Bahlol (Mediterranean Geoscience Reviews, 2026)

Engineered Spray-Dried PLGA-PEG Dual-Coated Micelles with Lactose/Trehalose Matrices for Pulmonary Doxorubicin Delivery: Achieving Sustained Release and Improved Aerosol Performance in NSCLC Therapy - Randa Mohammed Zaki; Alaa Ayman; Eman Mostafa Samy; Mahmoud Mohamed Omar; Obaid Afzal; Rawan Bafail; Waad A. Samman; Omiya A. Hasan (Journal of Pharmaceutical Innovation, 2026)

Personalized 3D-Printed Finger Splints Derived from CT Data Incorporating Multi-Drug Bilayer Nanofiber Delivery Systems - Ahmed M. Mortada; Alaa Y. Darwesh; Iman E. Taha; Thirupathi R. Anekalla; Nourhan Mostafa; Mohammed Maniruzzaman (AAPS PharmSciTech, 2026)

Efficacy and safety of lorundrostat in uncontrolled hypertension: a meta-analysis - Alaa Abdrabou Abouelmagd; Shrouk Ramadan; Mohamed Saad Sayed; Omar Abdulrahman Saad; Mazen Negmeldin Yassin; Alaa Mohammed Mostafa; Kerollos Abdelsayed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Lorundrostat, a novel selective aldosterone synthase inhibitor, has emerged as a potential treatment for uncontrolled hypertension. However, a comprehensive summary of its efficacy and safety profile is currently lacking. This meta-analysis aims to synthesize evidence from published randomized controlled trials (RCTs) to evaluate the clinical benefits and risks of lorundrostat in this patient population. Following the PRISMA guidelines, a systematic search was conducted on PubMed, Scopus, and Web of Science for RCTs comparing lorundrostat with placebo. The primary outcomes were changes from baseline in systolic and diastolic blood pressure. Data were pooled using a random-effects model to calculate mean differences (MD) for continuous outcomes and risk ratios (RR) for dichotomous outcomes, with corresponding 95% confidence intervals (CIs). Three RCTs comprising 1568 patients were included. Compared to placebo, lorundrostat significantly reduced both 24-h systolic blood pressure (MD: − 6.65 mmHg; 95% CI: [− 9.95 to − 3.35]) and office systolic blood pressure (MD: − 7.94 mmHg; 95% CI: [− 9.72 to − 6.15]). While the risk of serious adverse events was comparable, lorundrostat was associated with a higher incidence of hyperkalemia (RR: 5.47; 95% CI: [1.55 to 19.36]) and hyponatremia (RR: 1.95; 95% CI: [1.13 to 3.36]). Notably, lorundrostat significantly reduced the risk of adrenal insufficiency (RR: 0.15; 95% CI: [0.03 to 0.91]). Lorundrostat may be an effective agent for lowering blood pressure in patients with uncontrolled hypertension. Its safety profile is acceptable but requires careful monitoring of serum electrolytes and renal function. The reduced risk of adrenal insufficiency highlights its selectivity and potential as a valuable therapeutic option. Further large-scale, long-term studies are needed to confirm its sustained benefits and safety.

Optimization of UHPC with basil plant ash: Impacts on strength, durability, and gamma-ray attenuation - Sahar A. Mostafa; Islam N.Fathy; Alaa A. Mahmoud; Mohamed A. Abouelnour; K.A. Mahmoud; Shaaban M. Shaaban; Sameh A. Elhameed; Islam M. Nabil (Annals of Nuclear Energy, 2026)

Interactive effects of black sand and heat stress on coral reefs at Red Sea, Egypt - Alaa El-Din H. Sayed; Mohsen Y. Omer; Almountasirbellah Farrag; Rashad E.M. Said; Hamdy A.M. Soliman; Zeinab Bakr; Mostafa A. Khaled; Mohamed Abd El-Aal; Eman Saad; Mohamed Hamed (Marine Pollution Bulletin, 2026)

A comprehensive review on schizophrenia: epidemiology, pathogenesis, diagnosis, conventional treatments, and proposed natural compounds used for management - Alaa Anwar; Aya M. Mustafa; Kareem Abdou; Mostafa A. Rabie; Riham A. El-Shiekh; Ahmed M. El-Dessouki (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Schizophrenia (SCZ) is a complex, comprehensible mental condition that creates alienation from reality. SCZ is a mental disease, which is marked by progressive deficits in working memory, attention, and executive functioning. Because the disease’s etiology is unknown, current psychotherapy and pharmacological treatments merely treat symptoms and do not provide a cure. SCZ symptoms include hallucinations, delusions, disorganized behavior, and lack of desire. Long-term use of antipsychotic (antagonists at multiple G-protein-coupled receptors) (mGPCR antagonists) medicines for therapy has negative health consequences and discourages patients from taking regular medication. Ancient herbal therapies are regaining popularity in disease management due to their natural origins, less side effects, and cost-effectiveness. The various types of phytochemicals include alkaloids, glycosides, polyphenols, terpenes and terpenoids, phytosterols, cannabinoids, and carotenoids could be used as mGPCR antagonists. In this review, we documented the possibility of employing natural compounds as an alternative therapy to treat schizophrenia-related symptoms and cognitive impairments.

The use of Glutathione-S-transferase levels as marker of hepatic damage in chronic fasciolosis in cattle - Al-Hassan Mohammed Mostafa; Gehan Mohammed Sayed; Ali Ali Hassan Al-Ezzi; Alaa Eldin Kamal (Veterinary Parasitology, 2025)

Understanding the impact of spiral reinforcement on GFRP-RC beams under combined shear and torsion loading - Mohammed Gamal Gouda; Ibrahim T. Mostafa; Hamdy M. Mohamed; Alaa Sherif; Mohamed H. Agamy (Engineering Structures, 2025)

Mesoporous SiO2-chitin/MoO3 Nanocomposite: Synthesis, Surface Investigation, and Uptake Potential for Pb(II) and Cu(II) - Hany Fathy Heiba; Asia A. Taha; Alaa R. Mostafa; Abeer Elsaharty; Manal G. Mahmoud; Laila A. Mohamed (Environmental Processes, 2025)

Geochemistry of the U-bearing lithofacies within the major graben in Um Bogma area, Sinai, Egypt: implications for mineralization genesis and controlling factors - Ahmed E. Shata; Alaa Mostafa; Mahmoud M. Nasr; Ahmed M. Ismail; Hesham S. Serag El Din (Carbonates and Evaporites, 2025)

Full-scale assessment of biological performance of modified glass fiber reinforced polymer disk aerator in wastewater treatment plant - Tarek Mansour; Mohamed K. Mostafa; Rifaat Abdel Wahaab; Alaa Mohamed; Mostafa Moussa (Journal of Water Process Engineering, 2025)

UV-A-induced oxidative stress and immunotoxicity in African catfish (Clarias gariepinus): the bioremediation potential of Spirulina platensis for aquaculture - Mohamed Hamed; Carlos E. Monteiro; Rashad E. M. Said; Mostafa A. Abdel-Maksoud; Taghreed N. Almanaa; Mervat Naguib; Hanem S. Abdel-Tawab; Alaa Osman; Jae-Seong Lee; Alaa El-Din H. Sayed (Aquaculture International, 2025)

As nature's allies: Bee honey outperforms pomegranate and lemon juices in improving physio-biochemistry, antioxidants, RubisCO gene expression, and vase life of Calendula officinalis - Mostafa M. Rady; Marwa S.M. Habib; Ibrahim A.A. Mohamed; Hesham F. Alharby; Taia A.Abd El-Mageed; El‑Sayed M. Desoky; Alaa I.B. Abou-Sreea; Esmat F. Ali (South African Journal of Botany, 2024)

Impacts of climate change and black sand on Red Sea, Egypt. A comprehensive review - Mohamed Hamed; Mostafa A. Khaled; Rashad E.M. Said; Mohamed Abd El-Aal; Sobhi M. Ghoneim; Mohsen Y. Omer; Hamdy A.M. Soliman; Eman Saad; Zeinab Bakr; Jae-Seong Lee; Alaa El-Din H. Sayed (Regional Studies in Marine Science, 2024)

Patterns distribution, concentrations and sources of radioactive elements from black sand in the Red Sea coast, Egypt - Mohamed Hamed; Mostafa A. Khaled; Rashad E.M. Said; Sobhi M. Ghoneim; Eman Saad; Mohamed Abd El-Aal; Alaa El-Din H. Sayed (Journal of Hazardous Materials, 2024)

Towards the preparation of sustainable superplasticizers for geopolymeric pastes via radiation-induced grafting of sulfonic group-bearing monomers onto corn starch - Noha M. Deghiedy; Safaa M.A. El-Gamal; Mohamed Ramadan; Alaa Mohsen; Mahmoud M. Hazem; Mostafa A. Sayed; Fatma M. Helmy; Mona M. Wetwet; Ahmed E. Swilem (Carbohydrate Polymers, 2024)

Serum and Seminal Plasma Levels of Lead and Arsenic in Cigarette Smokers and Their Relation to the Semen Parameters - Azza Gaber Antar Farag; Eman Abd-Elfatah Badr; Alaa Osama Ali Kholif; Mostafa Nabil Khalifa; Mai Medhat Mohamed Ghanem (Biological Trace Element Research, 2024)
Male infertility along with altered semen parameters have been related to smoking. Smoking-related elevations in serum and seminal lead (Pb) and arsenic (As) may play a role in mediating the toxic effects of smoking on seminogram. This research aims to determine whether smoking has any significant impact on Pb and As levels in the seminal plasma and serum, as well as on the various semen parameters, when compared to nonsmokers. In total, 80 adult males were included: 60 smokers and 20 age-matched nonsmokers. Based on the number of cigarettes smoked/day (CPD), the smokers were categorized into mild (1–10), moderate (11–20), and severe (> 20). The analysis of semen was conducted in accordance with the 2010 WHO laboratory manual. Using an atomic absorption spectrophotometer, Pb and As concentrations in the serum and seminal plasma of all groups were determined. Compared to nonsmokers, smokers had a significantly reduced sperm count, motility, and viability, as well as a larger percentage of aberrant forms ( P = 0.001, 0.025, 0.034, 0.002 respectively). Smokers had higher Pb concentrations in their serum and seminal fluid than nonsmokers ( P = 0.002, 0.001 respectively). Seminal Pb had a significant negative correlation with sperm count ( P = 0.004, r = -0.320). Serum Pb levels were found to positively correlate with seminal Pb levels ( P 0.001, r = 0.648), and cigarette smokers had substantially greater seminal As levels than nonsmokers ( P = 0.024). Sperm viability was strongly inversely related to seminal As ( P = 0.042, r = -0.264). Seminal As levels and aberrant sperm shapes were found to be significantly correlated ( P = 0.001, r = 0.414). In smokers, a significant positive relationship between seminal As and seminal Pb was observed. Therefore, semen parameters could be adversely affected by smoking through high levels of Pb and As ( P = 0.012, r = 0.298).

Developing green slag/bentonite-based geopolymers modified with meso-porous tungsten oxide: Zeolitic phases, mechanical performance and gamma-radiation mitigation - M. Ramadan; S.M.A. El-Gamal; Mona M. Wetwet; Mostafa A. Sayed; M.M. Hazem; Noha M. Deghiedy; Ahmed E. Swilem; Alaa Mohsen (Applied Clay Science, 2024)

Mesoporous magnetic biochar derived from common reed (Phragmites australis) for rapid and efficient removal of methylene blue from aqueous media - Wael Ibrahim Mortada; Mahmoud Mohsen Ghaith; Nada Elsayed Khedr; Mostafa Ibrahim Ellethy; Alaa Waleed Mohsen; Amira Labib Shafik (Environmental Science and Pollution Research, 2024)
A novel mesoporous magnetic biochar (MBC) was prepared, using a randomly growing plant, i.e., common reed, as an exporter of carbon, and applied for removal of methylene blue (MB) from aqueous solutions. The prepared sorbent was characterized by nitrogen adsorption/desorption isotherm, saturation magnetization, pH of point of zero charges (pH PZC ), Fourier-transform infrared spectroscopy (FT-IR), and scanning electron microscopy (SEM). The obtained MBC has a specific surface area of 94.2 m 2 g −1 and a pore radius of 4.1 nm, a pore volume of 0.252 cm 3 g −1 , a saturation magnetization of 0.786 emu g −1 , and a pH PZC of 6.2. Batch adsorption experiments were used to study the impact of the physicochemical factors involved in the adsorption process. The findings revealed that MB removal by MBC was achieved optimally at pH 8.0, sorbent dosage of 1.0 g L −1 , and contact time of 30 min. At these conditions, the maximum adsorption was 353.4 mg g −1 . Furthermore, the adsorption isotherm indicated that the Langmuir pattern matched well with the experimental data, compared to the Freindlich model. The ∆ G was − 6.7, − 7.1, and − 7.5 kJ mol −1 , at 298, 308, and 318 K, respectively, indicating a spontaneous process. The values of ∆ H and ∆ S were 5.71 kJ mol −1 and 41.6 J mol −1 K −1 , respectively, suggesting endothermic and the interaction between MB and MBC is van der Waals type. The absorbent was regenerated and reused for four cycles after elution with 0.1 mol L −1 of HCl. This study concluded that the magnetic biochar generated from common reed has tremendous promise in the practical use of removing MB from wastewater. Graphic Abstract

Occurrence, distribution, and composition of black sand along the Red Sea, Egypt - Mohamed Hamed; Mohamed Abd El-Aal; Mostafa A. Khaled; Sobhi M. Ghoneim; Eman Saad; Jae-Seong Lee; Alaa El-Din H. Sayed (Science of The Total Environment, 2024)

Discovery of cytotoxic truncated vitamin D derivatives against both bortezomib‐sensitive and bortezomib‐resistant multiple myeloma phenotypes - Mohamed O. Radwan; Sawa Sakai; Alaa N. Hassan; Momoko Uesugi; Masaharu Sakamoto; Tsugumasa Toma; Mohammed A. S. Abourehab; Mostafa M. Badran; Hiroshi Tateishi; Nao Nishimura; Masami Otsuka; Mikako Fujita (Medicinal Chemistry Research, 2024)

Vitis vinifera L. seed standardized extract; a promising therapeutic against metabolic syndrome induced by high-fat/high-carbohydrate diet and streptozotocin in rats - Salma Mostafa Mohamed; Mostafa Abbas Shalaby; Riham A. El-Shiekh; Alaa F. Bakr; Maha M. Rashad; Shimaa R. Emam; Hossny A. El-Banna (South African Journal of Botany, 2024)

Potentially Toxic Element (PTE) Sources in the Middle Eocene Carbonate Aquifer, East El Minia, Egypt - Abdel-Aziz A. Abdel-Aziz; Salman A. Salman; Esam A. Ismail; Alaa Mostafa; Ramadan S. A. Mohamed (Water, Air, & Soil Pollution, 2024)
Water pollution with potentially toxic elements (PTEs) becomes a major threat to the validity of that water for drinking and agriculture and hence human life. The current study aims to evaluate the carbonate aquifer groundwater PTE content, sources, and impact on water quality. To achieve this goal, drilling cutoff of two wells and 30 groundwater samples were collected and chemically analyzed. The groundwater has TDS values ranged from 271.2 to 971.8 mg/l. Freshwater recharge process led to the continuous freshening of the aquifer and enhanced the forward ion exchange reactions. Carbonate and evaporate mineral dissolution/precipitation processes are the main controller of groundwater chemistry. Cd and As represented the most hazardous elements in these rocks followed by Pb. The presence of high concentrations of PTEs (As, Cd, Cr, and Pb) in water-bearing carbonate rocks has led to detritus of water quality and its unsuitability for drinking owing to the occurrence of these harmful elements in water. Even though the high concentrations of PTEs in the studied water, these elements occurred in low mobility and toxicity species: Fe(OH) 3 , Mn 2+ , (HAsO 4 ) −2 , Cd 2+ , Cr 2 O 3 , Cu 2 O, CuO, and PbCO 3 . This reflects the importance of studying element species rather than total concentration. Even though the unsuitability of this water for drinking owing to high concentrations of some PTEs, all of the samples were found to be suitable for irrigation.

Usage of natural wastes from animal and plant origins as adsorbents for the removal of some toxic industrial dyes and heavy metals in aqueous media - Afnan S. Batubara; Hamad M. Adress Hasan; Mohammed A. Abel Moniem; Mamdouh S. Masoud; Alaa-Eldin R. Mostafa; Mohammed Gamal; Mohamed A. Elsayed (Journal of Water Process Engineering, 2023)

Progress of synthetic cyclodextrins-based materials as effective adsorbents of the common water pollutants: Comprehensive review - Alaa T. Okasha; Ahmed A. Abdel-Khalek; Noof A. Alenazi; Ali A. AlHammadi; Wail Al Zoubi; Salh Alhammadi; Young Gun Ko; Mostafa R. Abukhadra (Journal of Environmental Chemical Engineering, 2023)

Isolated intracranial hypertension following SARS-CoV-2 infection in an adolescent boy: a case report - Alaa ELmazny; Shireen Mostafa Shousha; Samira Saraya; Rehab Magdy (Acta Neurologica Belgica, 2022)

Modeling COVID-19 effects on SDGs using system dynamics in Egypt - Mohamed Marzouk; Shimaa Azab; Nehal Elshaboury; Alaa Megahed; Mahmoud Metawie; Mostafa El Hawary; Doaa Ghaith; AbdElMoniem Bayoumi (Environmental Science and Pollution Research, 2022)
The coronavirus disease 2019 (COVID-19) poses a significant threat to achieving the Sustainable Development Goals (SDGs). To address this challenge, a thorough examination of the pandemic’s influence on four SDGs in Egypt is presented in a system dynamic model. The addressed goals are related to no poverty (SDG 1), zero hunger (SDG 2), decent work and economic growth (SDG 8), and climate action (SDG 13). The model is simulated over 35 years extending from 2015 to 2050. Furthermore, a web-based interactive learning environment is developed to analyze the interdependencies among public health activities and study the impacts of possible intervention countermeasures or prevention policies. Indicators including poverty line, food insecurity, gross domestic product (GDP) growth rate, and greenhouse gas (GHG) emissions are evaluated to track Egypt’s performance in relation to SDGs 1, 2, 8, and 13. According to the simulation model, the poverty line will continue to decline until it reaches around 16% by 2050. According to the significant governmental efforts to follow its vision of 2030, Egypt can achieve a decreasing percentage of food insecurity, reaching 3% in 2030, and this percentage will continue to decrease until it reaches full sufficiency by 2050. The GDP growth rate will rise every year until it reaches 13.71% in 2050. With respect to climate, GHG emissions are predicted to fall to roughly 97 Mt CO2-equivalents by 2050. This approach revitalizes debates about the achievement of SDGs amid the crisis and acts as a powerful tool that aids decision-makers in identifying leverage points to avoid the long-term negative repercussions of the crisis on the economy, people, and environment.

Depicting the main structural affected trends by operating aeromagnetic survey in the western part of Koraimat-Alzafarana road and surround area, Eastern Desert, Egypt - Alaa M. Eweis; Mostafa Toni; Alhussein Adham Basheer (Modeling Earth Systems and Environment, 2022)

Antidepressant potential of Mesembryanthemum cordifolium roots assisted by metabolomic analysis and virtual screening - Asmaa Abo Elgoud Said; Taha F. S. Ali; Eman Zekry Attia; Al-Shaimaa F. Ahmed; Alaa H. Shehata; Usama Ramadan Abdelmohsen; Mostafa Ahmed Fouad (Natural Product Research, 2021)

Phytoplankton dynamics and renewable energy potential induced by the environmental conditions of Lake Burullus, Egypt - Alaa A. Masoud; Mohamed M. El-Horiny; Hanan M. Khairy; Mostafa M. El-Sheekh (Environmental Science and Pollution Research, 2021)

Chemical and bacterial quality monitoring of the Nile River water and associated health risks in Qena–Sohag sector, Egypt - Mahmoud A. Abdelhafiz; Ahmed A. Elnazer; El-Montser M. Seleem; Alaa Mostafa; Ahmed G. Al-Gamal; Salman A. Salman; Xinbin Feng (Environmental Geochemistry and Health, 2021)

Protective roles of thymoquinone and vildagliptin in manganese-induced nephrotoxicity in adult albino rats - Heba El-Sayed Mostafa; Eman Ahmed Alaa El-Din; Dalia Abdallah El-Shafei; Nehal S. Abouhashem; Aisha Abdallah Abouhashem (Environmental Science and Pollution Research, 2021)

Risk assessment of heavy metals in drinking water on the human health, Assiut City, and its environs, Egypt - Elmontaser M. Seleem; Alaa Mostafa; Mohammed Mokhtar; Salman A. Salman (Arabian Journal of Geosciences, 2021)

Evaluation of Praziquantel Effectivenss After Decades of Prolonged Use in an Endemic Area in Egypt - Ramy Mohamed Ghazy; Mohamed Mostafa Tahoun; Sarah Mohamed Abdo; Ayman A. El-Badry; Noha Alaa Hamdy (Acta Parasitologica, 2021)

Synthesis of 3,3′-methylenebis(4-hydroxyquinolin-2(1H)-ones) of prospective anti-COVID-19 drugs - Ashraf A. Aly; Alaa A. Hassan; Asmaa H. Mohamed; Esraa M. Osman; Stefan Bräse; Martin Nieger; Mahmoud A. A. Ibrahim; Sara M. Mostafa (Molecular Diversity, 2021)

Evolution of the Paleocene–lower Eocene sedimentary basin in the Safaga–Quseir region, Eastern Desert, Egypt - Kamel H. Mahfouz; Nageh A. Obaidalla; Abdel Galil A. Hewaidy; Alaa Mostafa; Islam El-Sheikh (Arabian Journal of Geosciences, 2021)

Could curcumin ameliorate titanium dioxide nanoparticles effect on the heart? A histopathological, immunohistochemical, and genotoxic study - Eman Ahmed Alaa El-Din; Heba El-Sayed Mostafa; Mai A. Samak; Eman M. Mohamed; Dalia Abdallah El-Shafei (Environmental Science and Pollution Research, 2019)

Alleviative effect of licorice on copper chloride-induced oxidative stress in the brain: biochemical, histopathological, immunohistochemical, and genotoxic study - Heba El-Sayed Mostafa; Eman Ahmad Alaa-Eldin; Dalia Abdallah El-Shafei; Nehal S. Abouhashem (Environmental Science and Pollution Research, 2017)

Industrial oil wastewater treatment by free and immobilized Aspergillus niger KX759617 and the possibility of using it in crop irrigation - Eman H. F. Abd El-Zaher; Alaa M. Abou-Zeid; Azza A. Mostafa; Doaa M. Arif (Rendiconti Lincei. Scienze Fisiche e Naturali, 2017)

Local site effects estimated from ambient vibration measurements at the Nubian habitations area in Kurkur, Aswan, Egypt - R. E. Fat-Helbary; A. A. Abdel-latief; Alaa Mostafa; M. S. Arfa (Arabian Journal of Geosciences, 2016)

Risk posed by chlorinated organic compounds in Abu Qir Bay, East Alexandria, Egypt - Mohammed Abd EL-Hamid Khairy; Marit Kolb; Alaa R. Mostafa; Anwar EL-Fiky; Müfit Bahadir (Environmental Science and Pollution Research, 2012)

Spatial Distribution and Temporal Trends of Polycyclic Aromatic Hydrocarbons (PAHs) in Sediments from Lake Maryut, Alexandria, Egypt - Assem Omar. Barakat; Alaa Mostafa; Terry L. Wade; Stephen T. Sweet; Nadia B. El Sayed (Water, Air, & Soil Pollution, 2011)

Metal pollution records in core sediments of some Red Sea coastal areas, Kingdom of Saudi Arabia - Nadia B. E. Badr; Anwar A. El-Fiky; Alaa R. Mostafa; Bandr A. Al-Mur (Environmental Monitoring and Assessment, 2009)

Composition, distribution and sources of polycyclic aromatic hydrocarbons in sediments of the western harbour of alexandria, egypt - Alaa R. Mostafa; Assem O. Barakat; Yaorong Qian; Terry L. Wade (Journal of Soils and Sediments, 2003)